Does Shift in Vegetation Abundance After Nitrogen and Phosphorus Additions Play a Key Role in Regulating Fungal Community Structure in a Northern Peatland? - Cao, Chenhao; Huang, Jingjing; Ge, Leming; Li, Tong; Bu, Zhao-Jun; Wang, Shengzhong; Wang, Zucheng; Liu, Ziping; Liu, Shasha; Wang, Meng (Frontiers in Microbiology, 2022)
Soil fungal communities are key players in biogeochemical processes of peatlands, which are important carbon stocks globally. Though it has been elucidated that fungi are susceptible to environmental changes, little is known about the intricate and interactive effect of long-term nitrogen (N) and phosphorus (P) enrichment on fungal community structure in northern peatlands. In this study, we compared a short- (2 years) with a long-term (10 years) fertilization experiment in a peatland complex in northeastern China to assess how N and/or P additions influence fungal community structure. The results showed that fungal community composition and diversity were altered by N addition, without a significant interactive effect with P addition. Not only the long-term but also the short-term nutrient addition could change the abundance of different plant functional types. However, there were no strong cascading effects on fungal community in any of the fertilization experiments. Long-term nutrient addition showed a stronger effect on the relative abundance of different fungal functional guilds; an increase in the relative abundance of saprotrophs after fertilization did not jeopardize mycorrhizal fungi. Moreover, the decline in Sphagnum cover after long-term N addition did not parallel changes in the relative abundance of Sphagnum-associated fungi (Clavaria sphagnicola, Galerina tibiicystis, G. sphagnicola, and G. paludosa). Given that short- and long-term fertilization showed strongly contrasting effects on fungal community structure, our study highlights the necessity of assessing long-term effects of nutrient enrichment in the association between vegetation and fungal community in peatland ecosystems. Future research priorities should emphasize the connection between community structure of fungal functional guilds and their functionality, which is of paramount importance to better understand their influences on C storage in the face of uncertain N and P deposition regimes.